2005
DOI: 10.1111/j.1472-765x.2005.01635.x
|View full text |Cite
|
Sign up to set email alerts
|

Controlling production of brominated cyclic depsipeptides by Pseudoalteromonas maricaloris KMM 636T

Abstract: Aims: This study aims at evaluating the impact of the nutrient medium components on the in vitro production of the cytotoxic alterochromides. Methods and Results: The employment matrix-assisted laser desorption/ionization mass spectrometry (MALDI-MS) facilitated the identification of a range of brominated cyclic depsipeptides with molecular masses of 843/845, 857/859 and 922/924/926 Da, and 936/938/940 Da produced by the marine bacterium Pseudoalteromonas maricaloris KMM 636T . The fractions of cytotoxic yello… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 25 publications
(49 reference statements)
1
17
0
Order By: Relevance
“…P. maricolaris produces depsipeptide antibiotics, bromoalterochromides A and B. These substances are non extracellular products, but cell-bound substance (Ivanova et al 2002b;Sobolevskaya et al 2005). P. issachenkonii, P. piscicida and P. ruthenica produce antimicrobial substance in culture supernatant, but P. peptydolytica produces such substance as cell-bound product (Kalinovskaya et al 2004).…”
Section: Discussionmentioning
confidence: 97%
“…P. maricolaris produces depsipeptide antibiotics, bromoalterochromides A and B. These substances are non extracellular products, but cell-bound substance (Ivanova et al 2002b;Sobolevskaya et al 2005). P. issachenkonii, P. piscicida and P. ruthenica produce antimicrobial substance in culture supernatant, but P. peptydolytica produces such substance as cell-bound product (Kalinovskaya et al 2004).…”
Section: Discussionmentioning
confidence: 97%
“…Sobolevskaya et al [12] and Zheng et al [9] reported about the antimicrobial compounds extracted from Pseudoalteromonas strains isolated from marine sponges, while Isnansetyo and Kamei [27] deeply characterized the newly discovered P. phenolica, a bacterium producing anti-methicillin-resistant S. aureus substances. Finally, antimicrobial activity has been often associated with Pseudomonas species [16].…”
Section: Discussionmentioning
confidence: 98%
“…In particular, special attention has been directed to microorganisms isolated from invertebrates, such as sponges and algae [3 -9]. In some cases, bactericidal substances with novel chemical structures were purified and characterized [1,[10][11][12]. Nevertheless, in recent decades there has been a dearth of new classes of discovered antibiotics [5,13].…”
mentioning
confidence: 99%
“…Strains were also described as being able to inhibit the growth of yeast [9]. P. maricaloris, a close relative of P. piscicida isolated from the Coral Sea sponge Fascaplysinopsis reticulata, forms yellow colored dibromo-and bromoalterochomides ( Figure 5F) that possess antimicrobial activity and as well as cytotoxicity against the larvae of a sea urchin [95]. The algicidal strain Y, also closely related to P. piscicida, forms broad spectrum antimicrobial yellow brominated substances that LC-MS analysis revealed to comprise 12 different but likely structurally similar compounds.…”
Section: Low Molecular Weight Substancesmentioning
confidence: 99%